Cabo Pulmo and the Uróboro. A Multiscale Case of Socio-Environmental Perspectives - Torres Alvarez, Sebastian (2021)
This article presents the case study of Cabo Pulmo, a town located in Baja California Sur, Mexico, which went from an economy based on fishing and pearl extraction to one sustained by ecotourism. The objective is to analyze how this process was influenced by people and multiscale institutions. The ethnographic work consisted, first, in informal conversations with local inhabitants, followed by the application of in-depth interviews with three people, to obtain their life stories. To analyze the results, a metaphorical proposal based on the figure of the Ouroboros is used. The investigation focuses on a specific social group inserted in the globalized world, an environmental crisis with an adaptive response and articulated multiscale relationships for the consolidation of an ecotourism project and the defense of the territory against large tourist projects, also promoting socio-cultural changes. This case is considered a concrete example of how multiscale processes can influence local scenarios to promote adaptive responses, a topic associated with the discussions and challenges of climate change.